Penentuan Klaster Stasiun Hujan Menggunakan Analisis Komponen Utama (Studi Kasus di Daerah Istimewa Yogyakarta) - Putu Sudira (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
The geographical condition of Yogyakarta Special Region is varied from the mountainous plateau of the Southern part (Gunung Kidul) and the northern part (Sleman) as well as the boundary of the sea level along the southern part of the region. This condition causes the great variability of the amount of rainfall in this region. Related to this, the study aims at analyzing the rainfall data to determine the cluster of the raingauge stations based on the similar characteristics of the rainfall. The data needed for the analysis is the 15 years daily rainfall data from 67 raingauge stations including the location of the stations which are unevenly distributed in 4 districts available in Yogyakarta, namely: Gunung Kidul, Sleman, Kulon Progo, and Bantul. The Principal Component Analysis was used to analyze the data to determine the cluster of the raingauge stations. The results indicated that, by applying the similarity of 57 - 60%, the characteristics of rainfall in Yogyakarta could be categorized into 7 clusters.